The Matthean community"s state of coexistence between Jews and Gentiles - Shin, In-Cheol (HTS teologiese studies, 2019)
The past century has seen various studies on the nature of Matthew’s community, and conclusions are still being debated. The study on which this article is based acknowledges the past studies, but further proposes that the nature of the Matthean community was one of coexistence. The Matthean community implied in the book of Matthew coexisted in three ways. Firstly, Jews and Gentiles coexisted within the community: the Jewish–Christian-centred community had started to accept Gentiles and became a community where Gentiles and Jews lived together. Secondly, the community was in a state where both the Jewish law and the teachings of Jesus were followed. Finally, the community tended to set both Jews and Gentiles as targets for the mission. This means that there was missionary coexistence within the community. These three main reasons are the basis for the claim that the Matthean community maintained the nature of coexistence.